Agriculture Related Information Needs and their Fulfillment as Perceived by the Farmers in Bihar - Karan, Aditya; Ghosh, Souvik (Indian Journal of Extension Education, 2017)
The present study was conducted in Muzaffarpur and Madhubani districts of Bihar that included a random sample of 120  farmers, 60 each from both the districts. The farmers of Muzaffarpur and Madhubani districts were having varied  perceptions on information needs for most of the aspects in agriculture. However, farmers of both the districts perceived  maximum information needs for their capacity building/ training on different aspects of their farming. The farmers in  Muzaffarpur district attached importance to information needs in a decreasing order with agricultural inputs, agricultural  production technologies, agricultural finance, livelihood diversification options, agricultural marketing and post-harvest  management. While farmers of Madhubani district felt comparatively higher information needs for agricultural finance  followed by agricultural production technologies, agricultural inputs, livelihood diversification options, agricultural  marketing and post-harvest management. Farmers of Madhubani district have perceived five out of seven broad aspects of  agriculture at a less than average level on a 4-point continuum scale that may be attributed to the facts of poor socio demographic situation, agricultural backwardness as well as lack of adequate communication infrastructure in  Madhubani district. The step wise multiple regression models revealed that mass media use, education, family size and  household expenditure together have explained 53 per cent variation in farmers' perception on information needs. While,  mass media use, education, annual income, family size and personal localite sources use together have determined 61 per  cent variation in fulfillment of information needs with respect to various aspects of agriculture.
Keywords: Farmers' perceptions; Agricultural Information; Need Perception; Need Fulfillment